Chemical Sensors and Biosensors for Point-of-Care Testing of Pets: Opportunities for Individualized Diagnostics of Companion Animals - Fonseca, Wilson Tiago; Vello, Tatiana Parra; Lelis, Gabrielle Coelho; Deleigo, Ana Vitória Ferreira [UNESP]; Takahira, Regina Kiomi [UNESP]; Martinez, Diego Stéfani Teodoro; de Oliveira, Rafael Furlan [UNESP] (American Chemical Society (ACS), 2025)
Point-of-care testing (POCT) is recognized as one of the most disruptive medical technologies for rapid and decentralized diagnostics. Successful commercial examples include portable glucose meters, pregnancy tests, and COVID-19 self-tests. However, compared to advancements in human healthcare, POCT technologies for companion animals (pets) remain significantly underdeveloped. This Review explores the latest advancements in pet POCT and examines the challenges and opportunities in the field for individualized diagnostics of cats and dogs. The most frequent diseases and their respective biomarkers in blood, urine, and saliva are discussed. We examine key strategies for developing the next-generation POCT devices by harnessing the potential of selective (bio)receptors and high-performing transducers such as lateral flow tests and electrochemical (bio)sensors. We also present the most recent research initiatives and the successful commercial pet POCT technologies. We discuss future trends in the field, such the role of biomarker discovery and development of wearable, implantable, and breath sensors. We believe that advancing pet POCT technologies benefits not only animals but also humans and the environment, supporting the One Health approach.